Improving the classification of data deficient species in Red Lists: the case of the trigonal clam Tivela mactroides (Born, 1778) (Bivalvia) in São Paulo State - Rech, Thais Fonseca (2019)
Endangered species lists (or Red Lists) are useful tools for species conservation but, if inappropriately applied, they can be sources of conflict. This situation is aggravated for marine species, whose data deficiency is associated with the difficulties in the acquisition of information about the ecology of most organisms, especially invertebrates. In addition, lists can be made for different administrative levels (Global, National, Regional etc.) and, therefore, adequate information is needed for each of these scales. The list of endangered species of the State of São Paulo, Brazil, includes the trigonal clam Tivela mactroides, a beach bivalve used as food and recreation resource by inhabitants and tourists on the Northern Coast of the state. The lack of information on concepts and criteria to support inclusion in the state Red List and the potential negative consequences of this management tool to clam users raised concern on its application to T. mactroides. To overcome this data deficiency, we employed a stepped strategy to qualify information on its geographic distribution and trends in population size and potential threats. In this work, we developed a strategy of gathering information aiming to improve the categorization of this clam in the list of endangered species. We combined incremental steps considering review of literature and data repositories, simplified habitat suitability model, interviews with experts and local community, citizen science approach and beach validation visits. The combination of the employed methods revealed the occurrence of T. mactroides in 59 beaches, more than what could had been previously identified by traditional methods available (41 beaches) to the creation of Red Lists: Literature review, data repositories and experts. The literature was insufficient to inform the trends in population density and the possible threats. The overall temporal trends in the size of populations derived from interviews indicated a decrease, both for specific beaches and for the coastal as a whole. Waste water, oil spills and other pollutants were frequently mentioned, by both experts and communities, while clam capture was not cited as often as a threat. Considering that a species included in the List of Threatened Species of the State of São Paulo is protected from capture by law, the inclusion on the list might not offer full protection for T. mactroides due to the existence of multiple threats and the risk of habitat loss. An Ecosystem Based approach, facing both direct and indirect pressures on clam populations, would be the most adequate course of action to support conservation and sustainable use of Tivela mactroides. We demonstrated possible weaknesses and strengths of the methods, proposing that each method can be applied for conservation purposes depending on the characteristics of the project.